USE OF ARTIFICIAL INTELLIGENCE IN TEACHING PRACTICES: AN ANALYSIS - Dr Azmat Farooq Ahmad Khurram; Riaz Ahmad Muazzmi; Ms Sadaf Aslam; Ms Nadia Saleem (`, 2025)
This study was conducted to analyze the integration of Artificial Intelligence (AI) in educational practices over the past decade (2015-2024). Artificial Intelligence is rapidly and continuously reshaping teaching and learning. This research was conducted to explore how AI has increased paradigm shifts from inactive to dynamic learning, from vogue to personalized education, and from teacher-centered to student-centered. A mixed-method approach was employed to explore the implications of AI on teaching dynamics and student outcomes. Qualitative data were collected through literature review, surveys, interviews, and focus group discussions which were processed and analyzed by using NVivo, however, quantitative data were collected by employing a questionnaire. The findings indicate trends, and practices in vogue, and provide guidelines for teachers, officials, and shareholders on the successful integration of AI into learning. It is recommended that further research be conducted to find out further insight and depth to maximize AI’s worth use in pedagogy. Keywords: Artificial Intelligence, Teaching Practices, Analysis